The Effect of Leadership Styles on the Growth of Fintech Start-Ups in Zambia - Progress Choongo; Mungu Chileshe; Christine Nakamba Lesa; Bruce Mwiya; Thomas Kweku Taylor (FinTech, 2023)
The purpose of this study is to determine the relationship between the leadership styles of leaders of financial technology (Fintech) start-ups and firm growth. A quantitative design employing a cross-sectional survey with the use of a Likert questionnaire was conducted on the leaders of top-performing Fintech firms in Zambia, as recognized by Tracxn in its May 2020 report. This study focuses on three leadership styles: transformational leadership, transactional leadership, and laissez-faire leadership. The most significant result is that transformational leadership is strongly associated with the growth of Fintech start-ups in Zambia, while transactional leadership plays a limited role. The association between laissez-faire leadership and firm growth is positive but weak. The research makes two main contributions to the literature in the field of Fintech. First, the findings can help researchers explain leadership styles that predict the growth of Fintech start-ups. Second, founders of Fintech firms will understand the most important leadership styles that can lead to the growth of start-ups. The limitations of this study relate to the sample size, the need to consider other readership styles, and the use of qualitative and longitudinal designs that would provide more insights and validation.